Precisely designed perylene bisimide-substituted polyethylene with a high glass transition temperature and an ordered architecture1. Issue 84 (16th September 2015) - Song, Wei; Wu, Jianhua; Yang, Guangda; Han, Huijing; Xie, Meiran; Liao, Xiaojuan
<x xml:space="preserve">Abstract</x> A polyethylene with a precise repeat of perylene bisimide branches was synthesized by acyclic diene metathesis polymerization and hydrogenation of the as-synthesized polymer, and displayed good thermal stability and an ordered architecture.